An interannual study of foraging behaviour in sympatrically breeding macaroni Eudyptes chrysolophus and chinstrap penguins Pygoscelis antarcticus at Bouvetøya - Narvestad, Audun (UiT Norges arktiske universitet, 2019)
Species are likely to segregate their ecological niches to minimize competition for resources, but for centrally foraging predators that breed on sub-Antarctic islands in the Southern Ocean the possibility of niche segregation may be minimal. This study is the first to examine the spatial and trophic aspects of the foraging niche of sympatrically breeding macaroni and chinstrap penguins at the poorly-studied sub-Antarctic island Bouvetøya over multiple years. To measure at-sea movements and dive behavior, 90 breeding macaroni Eudyptes chrysolophus and 49 breeding chinstrap penguins Pygoscelis antarcticus were deployed with satellite transmitters and time-depth recorders over two austral summer breeding seasons, 2015 and 2018. In addition, tracked birds were sampled for blood for biogeochemical dietary analysis. Chinstrap penguins displayed large interannual variation in foraging behavior between the two years, and dove deeper, utilized larger foraging areas during late breeding stages and showed enriched values of δ15N in the first- compared to the second- year. Conversely, macaroni penguins dove to similar depths and displayed similar values of δ15N in both years. Our results suggest that potentially low krill abundances in the waters around Bouvetøya in 2015 forced the chinstrap penguins to search for alternative prey, like myctophid fishes, which resulted in increased overlap in the two species' foraging niche. Consequently, the chinstrap penguins may have faced increased interspecific competition for prey or catabolism from food shortage. Irrespective, our findings may partly explain the decreasing number of breeding chinstrap penguins at the world's most remote island, Bouvetøya.
Keywords: Bouvetøya; biokjemi; biotelemetri; marin biologi; pingviner; zoologi

PFAS bioaccumulation in Antarctic breeding south polar skua (Catharacta maccormicki) and its prey items - Alfaro Garcia, Laura Andrea; Borgå, Katrine (Universitetet i Oslo, 2018)
Per- og polyfluorerte alkylstoffer (PFAS) har blitt funnet i blodprøver fra sørjo (Catharacta maccormicki) tatt i løpet av hekkesesongen i kolonien i Svarthamaren (Dronning Mauds land, Antarktis). For å undersøke om disse konsentrasjonene i sørjo stammer fra dietten i hekkesesongen, sammenligner denne oppgaven biomagnifisering i to næringskjeder. Ved innenlands kolonien Svarthamaren spiser sørjoene nesten utelukkende egg og unger fra antarktisk petrell (Thalassoica antarctica), og petrellene spiser fisk og krepsdyr. I den kystnære kolonien ved Dumont D’Urville (DDU, Adélie Land), spiser sørjoene hovedsakelig egg og unger fra Adélie pingviner (Pygoscelis adeliae). Væskekromatografi-massespektrometri (LC/MS) ble brukt for å måle PFAS i mageinnhold og egg fra antarktisk petrell, og i blodprøver fra sørjo, Adélie pingvin-unger, og antarktisk petrellunger og -voksne. Stabile isotoper (δ13C and δ15N) ble også analysert som diettdeskriptorer. Resultatene ble slått sammen med resultater fra tidligere studier fra begge koloniene for å oppnå et datasett for sørjo og dens diett ved både Svarthamaren og DDU. Datasettet ble brukt for å beregne biomagnifiseringsfaktor (BMF) og trofisk magnifisering faktor (TMF) for de detekterte PFASene i de to næringskjedene. Ved Svarthamaren var PFUnA over deteksjonsgrensen i alle matriksene, men var ikke tilstede i enkelte prøver. Andre detekterte PFASer var Perfluoroktyl sulfonat (PFOS), Perfluorononanoate (PFNA), Perfluorodecanoate (PFDcA), Perfluoroundecanoate (PFUnA), Perfluorododecanoate (PFDoA), Perfluorotridecanoate (PFTriA) and Perfluorotetradecanoate (PFTeA). PFAS konsentrasjonene økte oppover i næringskjeden, hvorav nivåene for alle detekterte PFASer var høyest hos sørjo. Ved DDU var PFAS konsentrasjonene lavere, men mønsteret var sammenlignbart med det i Svarthamaren. Forgrenet PFOS ble kvantifisert i sørjo fra DDU, men var ikke over deteksjonsgrense i andre matrikser. Byttedyrene hadde flere PFASer over deteksjonsgrensen i Svarthamaren sammenliknet med DDU. Vi beregnet BMF og TMF for alle detekterte PFASer i Svarthamaren, men kun for PFOS, PFNA, PFDcA og PFUnA i DDU fordi bare disse ble funnet i både sørjo og pingvinene. BMF for PFOS var høyere enn forventet i vanlige predator-bytte forhold i begge koloniene, noe som peker på en ukjent kilde. Biomagnifikasjonsverdiene for andre PFASer var varierende, men sammenliknbare mellom koloniene. PFAS-konsentrasjonene i sørjo fra begge kolonier og i antarktisk petrell reflekterer sannsynligvis eksponering utenfor Antarktis i løpet av vinteren. De detekterte konsentrasjoner i Adélie pingviner er ikke høye nok for å forklare de høye PFAS-nivåene i sørjoene i DDU. Derfor, i DDU, disse PFAS-nivåer kommer fra andre byttedyr enten innenfor regioner eller mest sannsynligvis fra utenfor Antarktis.
Keywords: Dronning Maud Land; kjemiske analyser; ornitologi; petreller; pingviner; sjøfugler; toksikologi

A preliminary survey of the terrestrial arthropods of the Rosenthal Islands, Antarctica - Gantz, J D; Spacht, Drew E; Lee, Richard E (Polar Research, 2018)
The Rosenthal Islands lie along the western edge of the Antarctic Peninsula. They are largely inaccessible and the few research projects in the area have focused on seabird colonies, so nothing has been known about the arthropod fauna on these islands. We conducted a preliminary survey of the arthropods associated with large penguin colonies. We identified two species of Collembola (Cryptopygus antarcticus and Friesea grisea), four species of mites (Alaskozetes antarcticus, Hydrogamasellus racovitzai, Tectopenthalodes villosus and Rhagidia sp.) and one insect (Belgica antarctica). The mite A. antarcticus and the collembolan C. antarcticus were common in large aggregations at our collecting sites and were occasionally observed on the surface of penguin guano without vegetative cover. The insect, a chironomid midge, was less common and found only in vegetated areas.
Keywords: Antarktis; biologi; fauna; leddyr; midder; pingviner; zoologi

The relationship between coastal weather and foraging behaviour of chinstrap penguins, Pygoscelis antarctica - Lowther, Andrew D; Trathan, Phil; Tarroux, Arnaud; Lydersen, Christian; Kovacs, Kit M (ICES Journal of Marine Science, 2018)
There is increasing interest in using higher-trophic level predators as ecosystem indicators because their performance is presumed to be linked to the overall function of the ecosystem that supports them. In the southwest Atlantic sector of the Southern Ocean, Antarctic krill (Euphausia superba) supports huge predator populations as well as a growing commercial fishery. To utilize information from the ecosystem in an adaptive framework for sustainably managing krill catch levels, performance indices of krill predators have been proposed as a proxy for krill abundance. However, there are several potentially confounding sources of variability that might impact predator performance such as the effects of environmental variability and fishing pressure on krill availability at scales relevant to predators. In this context, our study capitalises on the occurrence of an unexpected El Niño event to characterise how environmental variability can drive changes in predator foraging behaviour. We demonstrate a clear link between coastal downwelling and changes in the at-sea habitat usage of chinstrap penguins (Pygoscelis antarctica) foraging in a local krill fishing area. Penguins tracked from their breeding colonies on Powell Island, Antarctic Peninsula, undertook fewer, longer foraging trips during the downwelling-affected season compared with the season where no such downwelling was detected, suggesting that changes in climate-driven oceanography may have reduced krill availability along the northern shelf of the island. Our study demonstrates that penguin foraging behaviour is modified by scale-dependent processes, which if not accounted for may result in erroneous conclusions being drawn when using penguins as bioindicators of krill abundance.
Keywords: Sørishavet; marinbiologi; meteorologi; ornitologi; pingviner; økologi

Chinstrap penguin population genetic structure: one or more populations along the Southern Ocean? - Mura-Jornet, Isidora; Pimentel, Carolina; Dantas, Gisele P M; Petry, Maria Virginia; González-Acuña, Daniel; Barbosa, Andrés; Lowther, Andrew D; Kovacs, Kit M; Poulin, Elie; Vianna, Juliana A (BMC Evolutionary Biology, 2018)
Keywords: Bouvetøya; Sørishavet; fugler; genetikk; marin biologi; ornitologi; pingviner

Temporal variation in trophic relationships among three congeneric penguin species breeding in sympatry - Tarroux, Arnaud; Lydersen, Christian; Trathan, Philip N; Kovacs, Kit M. (Ecology and Evolution, 2018)
Penguins are a monophyletic group in which many species are found breeding sympatrically, raising questions regarding how these species coexist successfully. Here, the isotopic niche of three sympatric pygoscelid penguin species was investigated at Powell Island, South Orkney Islands, during two breeding seasons (austral summers 2013–2014 and 2015–2016). Measurements of carbon (δ13C) and nitrogen (δ15N) stable isotope ratios were obtained from blood (adults) or feather (chicks) samples collected from Adélie Pygoscelis adeliae, chinstrap P. antarctica, and gentoo P. papua penguins. Isotopic niche regions (a proxy for the realized trophic niches) were computed to provide estimates of the trophic niche width of the studied species during the breeding season. The isotopic niche regions of adults of all three species were similar, but gentoo chicks had noticeably wider isotopic niches than the chicks of the other two species. Moderate to strong overlap in isotopic niche among species was found during each breeding season and for both age groups, suggesting that the potential for competition for shared food sources was similar during the two study years, although the actual level of competition could not be determined owing to the lack of data on resource abundance. Clear interannual shifts in isotopic niche were seen in all three species, though of lower amplitude for adult chinstrap penguins. These shifts were due to variation in carbon, but not nitrogen, isotopic ratios, which could indicate either a change in isotopic signature of their prey or a switch to an alternative food web. The main conclusions of this study are that (1) there is a partial overlap in the isotopic niches of these three congeneric species and that (2) they responded similarly to changes that likely occurred at the base of their food chain between the 2 years of the study.
Keywords: Antarktis; fôring; hekkekoloni; klimaendringer; krill; miljøendringer; pingviner; plankton; stabile isotoper; zoologi

Investigation of Babesia sp. in pygoscelid penguins at the South Shetland Islands - Thijl Vanstreels, Ralph Eric; Ferreira Junior, Francisco C; de Angeli Dutra, Daniela; Epiphanio, Sabrina; Braga, Érika M; Pistorius, Pierre A; Catão-Dias, José Luiz (Polar Research, 2018)
Babesia spp. are tick-borne parasites, and 16 avian-infecting species have been described to date, including one species ( Babesia peircei ) that infects penguins. Considering the results of a recent study reporting Babesia sp. in penguins on Deception Island, South Shetland Islands, we re-examined the samples obtained in a previous investigation on the occurrence of blood parasites in adult Adélie ( Pygoscelis adeliae ), chinstrap ( Pygoscelis antarcticus ) and gentoo penguins ( Pygoscelis papua ) on King George and Elephant islands, South Shetland Islands. Notwithstanding a comprehensive re-examination of the blood smears, Babesia sp. was not detected. When we employed two nested PCR tests targeting the 18S rRNA gene of Babesia , a considerable proportion of the samples produced positive results; however, gene sequencing revealed these were due to cross-amplification of non-target organisms. We therefore did not detect Babesia sp. infection in penguins on King George and Elephant islands. Additional studies will be valuable to clarify the distribution and epidemiology of tick-borne pathogens in sub-Antarctic and Antarctic seabirds.
Keywords: Antarktis; biologi; epidemiologi; ornitologi; parasitter; pingviner; sjøfugler; zoologi

Versatility of GC-Orbitrap mass spectrometry for the ultra-trace detection of persistent organic pollutants in penguin blood from Antarctica - Warner, Nicholas; Cojocariu, Cristian; Scientific, ThermoFisher (2018)
Using GC Orbitrap mass spectrometry to address analytical challenges with trace level detection of persistent organic pollutants in Antarctica.
Keywords: Antarktis; biologi; miljøgifter; pingviner; zoologi

An enigmatic fossil penguin from the Eocene of Antarctica - Jadwiszczaka, Piotr; Mörs, Thomas (Polar Research, 2017)
Tarsometatarsi are key skeletal elements in penguin palaeontology. They constitute, among others, type specimens of all 10 widely accepted species of fossil penguins from the Eocene La Meseta Formation on Seymour Island (Graham Land, Antarctic Peninsula). Here, we report on a recently collected large-sized tarsometatarsus from this formation that represents a new morphotype. We are convinced that the morphotype corresponds to a new species, but the material is too scarce for a taxonomic act. Undoubtedly, the bone discussed here is a valuable addition to our knowledge on diversity of early penguins.
Keywords: Antarktis; fossiler; paleobiologi; paleontologi; pingviner

Gastrointestinal helminths of Adélie penguins (Pygoscelis adeliae) from Antarctica - Diaz, Julia Inés; Fusaro, Bruno; Longarzo, Lucrecia; Coria, Néstor Rubén; Vidal, Virginia; D'Amico, Verónica; Barbosa, Andrés (Polar Research, 2016)
Knowledge about parasitic organisms in Antarctica is scarce and fragmentary. The study reported here adds to the knowledge of gastrointestinal parasites of the Adélie penguin (Pygoscelis adeliae) (Sphenisciformes), from 25 de Mayo/King George Island (South Shetlands), Bahia Esperanza (Hope Bay) and Avian Island (Antarctica). Thirty-five freshly dead specimens (20 chicks and 15 adults) were collected from December 2007 to December 2014 and examined for internal macroparasites. Three adult parasite species were found: one Cestoda, Parorchites zederi, and two Nematoda, Stegophorus macronectes and Tetrameres sp. Immature Tetrabothrius sp. were found in hosts from Avian Island. Helminth communities are known to be related to host feeding behaviours. Low parasite richness observed in Adélie penguins could be related to the stenophagic and pelagic diet of this host species, which feeds almost exclusively on krill. Keywords: Parorchites zederi; Stegophorus macronectes; Tetrameres sp.; parasites; ecosystem health.
Keywords: Antarktis; krill; parasitter; pingviner; plankton; zoologi; økosystemer

Regurgitation of the koilin layer in chinstrap penguins (Pygoscelis antarcticus) and its association with gastric parasites - Kim, Han-Kyu; Choi, Chang-Yong; Jeong, Min-Su; Kang, Hwa-Yeon; Lee, Woo-Shin (Polar Research, 2016)
The koilin membrane, formed by the secretions of the ventricular and pyloric glands, functions as a protective layer in the gizzards of most bird species. However, the ecological functions of koilin have never been studied in free-ranging penguins. During the two austral summers from 2012 to 2014, we observed the regurgitated koilins of chinstrap penguins (Pygoscelis antarcticus) at Narębski Point on King George Island, South Shetland Islands, and we detected a significant difference in the daily accumulation of regurgitated koilins between the pre-hatching and post-hatching periods in the rookery. We also found 233 gastrointestinal parasites, all Stegophorus macronectes (Nematoda, Acuariidae), from 26 out of 45 koilins freshly regurgitated by chinstrap penguins. We suggest that the regurgitation of koilins may benefit adult chinstrap penguins in the wild by reducing parasitic loads when they fast during incubation; it may also help decrease the risk of parasite transmission to chicks. Our results present the first observations of regurgitated koilins among breeding chinstrap penguins. How koilin regurgitation functions in penguins requires further study. Among the gentoo penguins (P. papua) co-occurring at the study site, we observed no regurgitated koilin layers. Keywords: Cuticula gastris; host-parasite interaction; nematodes; parasitic load; regurgitation; Stegophorus macronectes.
Keywords: Antarktis; biologi; gastrointestinale parasitter; ornitologi; pingviner; zoologi

Chinstrap and macaroni penguin diet and demography at Nyrøysa, Bouvetøya - Niemandt, Corne; Kovacs, Kit M; Lydersen, Christian; Dyer, Bruce M; Isaksen, Kjell; Hofmeyr, G J Greg; Mehlum, Fridtjof; de Bruyn, P J Nico (Antarctic Science, 2016)
Keywords: Bouvetøya; klimaendringer; krill; pelsseler; pingviner; plankton

Haematological values of three Antarctic penguins: gentoo (Pygoscelis papua), Adélie (P. adeliae) and chinstrap (P. antarcticus) - Ibañez, Andrés E; Najle, Roberto; Larsen, Karen; Pari, Marcela; Figueroa, Amalia; Montalti, Diego (Polar Research, 2015)
It is established that haematological and biochemical parameters provide important data to assess the physiological condition and health status of wild birds. To undertake conservation physiology or ecophysiology work, it is therefore essential to establish baseline physiological parameters and how these parameters change with age and life history events. In this work, we determined and compared baseline haematology and serum biochemistry between adults and chicks of three Antarctic penguin species of the genus Pygoscelis: gentoo (P. papua), Adélie (P. adeliae) and chinstrap (P. antarcticus). Differences in adults among species were observed in haemoglobin and biochemical parameters such as total proteins, glucose and alkaline phosphatase activity. In addition, differences between adults and chicks in haematocrit, haemoglobin, total proteins and glucose concentration were determined. Moreover, we evaluated the electrophoretic protein profiles between adults and chicks of the genus Pygoscelis, and a conserved protein pattern was observed among species and ages in the genus. Altogether, the results suggest that biochemical and haematological differences among pygoscelids may be related to the nutritional status and energetic expenditure during breeding as well as their feeding habits and development stage. Keywords: Antarctic; haematology; physiology; Pygoscelis; penguins; serum biochemistry.
Keywords: Antarktis; biokjemi; biologi; fysiologi; hematologi; pingviner; zoologi

At the root of the early penguin neck: a study of the only two cervicodorsal spines recovered from the Eocene of Antarctica - Jadwiszczak, Piotr (Polar Research, 2014)
The spinal column of early Antarctic penguins is poorly known, mainly due to the scarcity of articulated vertebrae in the fossil record. One of the most interesting segments of this part of the skeleton is the transitional series located at the root of the neck. Here, two such cervicodorsal series, comprising reinterpreted known material and a new specimen from the Eocene of Seymour Island (Antarctic Peninsula), were investigated and contrasted with those of modern penguins and some fossil bones. The new specimen is smaller than the counterpart elements in recent king penguins, whereas the second series belonged to a large-bodied penguin from the genus Palaeeudyptes. It had been assigned by earlier researchers to P. gunnari (a species of “giant” penguins) and a Bayesian analysis—a Bayes factor approach based on size of an associated tarsometatarsus—strongly supported such an assignment. Morphological and functional studies revealed that mobility within the aforementioned segment probably did not differ substantially between extant and studied fossil penguins. There were, however, intriguing morphological differences between the smaller fossil specimen and the comparative material related to the condition of the lateral excavation in the first cervicodorsal vertebra and the extremely small size of the intervertebral foramen located just prior to the first “true” thoracic vertebra. The former feature could have resulted from discrepancy in severity of external pneumatization. Both fossils provided valuable insights into the morphology and functioning of the axial skeleton in early penguins. Keywords: Antarctic Peninsula; La Meseta Formation; Palaeogene; early Sphenisciformes; cervicodorsal vertebrae.
Keywords: Antarktis; biologi; fossiler; morfologi; paleogen; pingviner

Post-breeding at-sea movements of three central-place foragers in relation to submesoscale fronts in the Southern Ocean around Bouvetøya - Lowther, Andrew D; Lydersen, Christian; Biuw, Martin; de Bruyn, P J Nico; Hofmeyr, Greg J G; Kovacs, Kit M (Antarctic Science, 2014)
Keywords: Bouvetøya; oseanografi; pelsseler; pingviner; satellitt; telemetri

At-sea behaviour of three krill predators breeding at Bouvetøya—Antarctic fur seals, macaroni penguins and chinstrap penguins - Blanchet, Marie-Anne; Biuw, Martin; Hofmeyr, Greg; de Bruyn, P. J. Nico; Lydersen, Christian; Kovacs, Kit M. (Marine Ecology Progress Series, 2013)
Keywords: Bouvetøya; krill; pelsseler; pingviner; pinnipedier; plankton; seler; zoologi

Using visible reflectance spectroscopy to reconstruct historical changes in chlorophyll a concentration in East Antarctic ponds - Chen, Qianqian; Liu, Xiaodong; Nie, Yaguang; Sun, Liguang (Polar Research, 2013)
The visible reflectance spectroscopy (VRS) and chlorophyll a concentration were determined in three sediment profiles collected from East Antarctica to investigate the potential application of VRS in reconstructing historical changes in Antarctic lake primary productivity. The results showed that the appearance of a trough at 650–700 nm is an important marker for chlorophyll a concentration and can therefore be used to distinguish the sedimentary organic matter source from guano and algae. The measured chlorophyll a content had significant positive correlations with the trough area between 650 and 700 nm, and no distinct trough was found in the sediments with organic matter completely derived from guano. Modelling results showed that the spectra spectrally inferred chlorophyll a content, and the measured data exhibit consistent trends with depth, showing that the dimensionless trough area can serve as an independent proxy for reconstructing historical fluctuations in the primary production of Antarctic ponds. The correlation of phosphorus (P) with measured and inferred chlorophyll a contents in ornithogenic sediments near penguin colonies indicates that the change in primary productivity in the Antarctic ponds investigated was closely related to the amount of guano input from these birds. Keywords: Reflectance spectroscopy; ornithogenic sediments; chlorophyll a; Antarctic ponds; primary productivity; VRS.
Keywords: Antarktis; alger; biogeokjemi; fytoplankton; innsjø; pingviner; sedimenter; sjøfugler

Better late than never? Interannual and seasonal variability in breeding chronology of gentoo penguins at Stranger Point, Antarctica - Juáres, Mariana A; Santos, M Mercedes; Negrete, Javier; Santos, M Rita; Mennucci, Jorge A; Rombolá, Emilce; Longarzo, Lucrecia; Coria, Néstor R; Carlini, Alejandro R (Polar Research, 2013)
Rapid climate change recorded in the western Antarctic Peninsula confronts species with less predictable conditions in the marine and terrestrial environments. We analysed the breeding chronology and nesting site selection of gentoo penguins (Pygoscelis papua) at King George Island (Isla 25 de Mayo), Antarctica, during four seasons in which differences in snow presence and persistence on the ground were observed. We recorded an overall delay as well as seasonal asynchrony at the beginning of reproduction for those years with higher snow deposition. A redistribution of breeding groups was also observed. Nevertheless, the population breeding success and chicks’ weight at fledging remained relatively constant, despite the delay in breeding chronology, the increased duration of foraging trips during the guard stage and the decreased weight of stomach contents during the crèche stage. We suggest that the plasticity of their trophic biology, along with the flexibility of their breeding phenology and relocation of breeding groups, may be complementary reasons why gentoo penguin populations in the region have remained stable in spite of the changing conditions currently registered. Keywords: Antarctica; breeding delay; breeding phenology; snow; Pygoscelis papua; Euphausia superba.
Keywords: Antarktis; klimaendringer; krill; observasjoner; pingviner; plankton; reproduksjon; snø; zoologi

Long-range migration of a chinstrap penguin from Bouvetøya to Montagu Island, South Sandwich Islands - Biuw, Martin; Lydersen, Christian; Nico de Bruyn, P. J.; Arriola, Aline; Hofmeyr, Greg G. J.; Kritzinger, Petrus; Kovacs, Kit M. (Antarctic Science, 2010)
We describe a long-range migration of a pre-moulting adult chinstrap penguin from Bouvetøya, a small relatively recently established colony, to the South Sandwich Islands, where large, established colonies of this species reside. The trip lasted around three weeks, covered ∼3600 km, and the time of arrival was consistent with the annual moult. The bird did not travel along the shortest path or along a constant bearing, but instead followed what appeared to be a series of two or three rhumb lines of constant bearing. Small southward and northward deviations from the general path were consistent with local water currents. Travel speeds were high during daylight but decreased at night, suggesting that resting or opportunistic feeding occurred preferentially at night. While long-range winter migrations of chinstraps to feeding areas in the vicinity of distant colonies have been previously described, this is the first observation of such a trip during the period between breeding and moulting, and the first record of an individual actually arriving at one of these distant colonies. This has implications for understanding population structure and management of this important Southern Ocean predator.
Keywords: Bouvetøya; NARE 2007/08; Sør-Sandwichøyene; marin biologi; pingviner; sjøfugler